Shamanism in Tuva and Okinawa: similarities and distinctions - Mongush, Marina V. (The New Research of Tuva, 2013)
The article studies similarities and distinctions between Tuvan and Japan’s southern Prefecture of Okinawa’s Shamanism. The basic attention is paid to a social role of the shaman in a society, outpouring of "shaman disease”, ceremonial practice, persecutions on shamans in Tuva and on Okinawa in different periods.
Keywords: Tuva; Okinawa; shamanism; cult ceremony; comparative study; religious beliefs